JAEPL, Vol. 2, Winter 1996-1997 - Alice G. Brand (Editor) (Journal of the Assembly for Expanded Perspectives on Learning, 1996)
Essays Jean Trounstine. Sacred Spaces. Drama in the prison classroom teaches that transgression can enhance spirituality. Irene Papoulis. Spirituality and Composition: One Teacher's Thoughts. The author explores her ambivalence about combining her interest in spirituality and her composition teaching. George Kalamaras. Meditative Silence and Reciprocity: The Dialogic Implications for 'Spiritual Sites of Composing. Recent studies of silence must focus on the dialogical nature of Eastern meditation, examining the values of meditative awareness and social theories of reciprocity. Christopher Ferry. When the Distressed Teach the Oppressed: Toward an Understanding of Communion and Commitment. Jane Tompkins' adaptation of Paulo Freire's educational philosophy is critiqued through exploring the spiritual basis of his idea of the "Easter experience." Mary Buley-Meissner. Diversity and Dialogue in Reforming the Academic Community. Affirming multiculturalism in higher education should include discussions of students' spiritual diversity. Arlette Ingram Willis and Shuaib J. Meacham. Break Point: The Challenges of Teaching Multicultural Education Courses. Teaching multicultural education courses to preservice teachers exacts an emotional toll as they begin to acknowledge their ethnic awareness. John Ramey. Transcending Gender: A New Awareness of the Fluid Self in Writing. The constructs of the male and female in the gendered self are not binary opposites but interlocking halves of an inseparable whole. Margaret Batschelet and Linda Woodson. From Writers to Writer/Designers. Instructors should extend the idea of thought in word only to possibilities offered by the visual. Dennis Young. Re-Visioning Psychology in the Writing Class. With its emphasis on soul-work and the imaginal frames of psyche, archetypal psychology helps teachers more fully interpret the motivations and intricacies of writing and learning. Emily Nye. Aiding AIDS Through Writing: A Study and Bibliography. A writing group at an HIV clinic generated four kinds of narratives, each with a different healing function. A selected bibliography follows.